Pemberdayaan Perempuan Fatayat NU Windusari Magelang Melalui Pelatihan Pemasaran Digital Facebook Marketplace - Taujiharrahman, Darma; Novita, Yeyen; Achmad Nur Alfianto; Khusni, Kholilatul; Herawati, Mesi (Yayasan Sagita Akademia Maju, 2025)
In the digital era, women entrepreneurs must be equipped with relevant digital skills to enhance their business potential. Many women’s business groups still face challenges in utilizing technology, particularly in marketing their products online. This community service initiative aimed to strengthen the digital marketing capabilities of women from Fayat NU Windusari, Magelang, through training focused on the use of Facebook as a promotional tool. Using a Participatory Action Research (PAR) approach, the program emphasized collaborative learning and direct practice, enabling participants to better understand and apply Facebook features for marketing purposes. The training covered content creation, product promotion, and interaction with potential customers via social media. As a result, the participants showed improved knowledge and skills in leveraging Facebook for business activities. This activity illustrates the importance of digital empowerment for women, enabling them to expand market access, increase income, and sustain their entrepreneurial efforts in the digital age.